Particle Production via Dirac Dipole Moments in the Magnetized and Nonmagnetized Exponentially Expanding Universe - Semra Gurtas Dogan; Ganim Gecim; Yusuf Sucu (Advances in High Energy Physics, 2019)
In the present paper, we solve the Dirac equation in the 2+1 dimensional exponentially expanding magnetized by uniform magnetic field and nonmagnetized universes, separately. Asymptotic behaviors of the solutions are determined. Using these results we discuss the current of a Dirac particle to discuss the polarization densities and the magnetization density in the context of Gordon decomposition method. In this work we also calculate the total polarization and magnetization, to investigate how the magnetic field affects the particle production. Furthermore, the electric and the magnetic dipole moments are calculated, and based on these, we have discussed the effects of the dipole moments on the charge distribution of the universe and its conductivity for both the early and the future time epoch in the presence/absence of a constant magnetic field and exponentially expanding spacetime.